PRINCIPAL LEADERSHIP BASED ON THE MOTTO OF KALTENG BERKAH AT SMAN KOTA PALANGKARAYA (MULTI-SITE STUDY AT SMAN 1 PALANGKARAYA AND SMAN 2 PALANGKARAYA) - Zenfrianto, Zenfrianto; Suriansyah, Ahmad; Aslamiah, Aslamiah (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
School principal leadership based on the KALTENG BERKAH motto reflects the values of Dignity (Bermartabat), Elegance (Elok), Religiousness (Religius), Strength (Kuat), Trustworthiness (Amanah), and Harmony (Harmonis). These local values are relevant to education in shaping a harmonious school environment and student character. The values of strength and trustworthiness play a vital role in addressing educational challenges. This study focuses on: (1) the leadership strategies of school principals based on the KALTENG BERKAH motto at public senior high schools in Palangkaraya City, Central Kalimantan Province, and (2) the leadership innovations of school principals grounded in the KALTENG BERKAH motto. The research approach is qualitative, employing both written and verbal informant data, as well as direct observation. The researcher visited the sites to obtain more comprehensive data. Data were collected using individual analysis, cross-site analysis, and proposition techniques. The findings indicate that the school principals' leadership strategies emphasize decision-making grounded in the KALTENG BERKAH motto by integrating character values into learning processes, fostering religious, courteous, disciplined, clean, and hardworking attitudes to develop leadership character. Leadership innovations highlight democratic and transformational approaches, emphasizing integrity and collaboration that reflect dignity, religiousness, harmony, and strong partnerships with teachers, school committees, and parents. Theoretical implications: Both principals employed democratic and transformational leadership styles that accentuate integrity, dignified collaboration, religiousness, and harmony. Practical implications: Graceful and strong leadership aligned with the BERKAH values promotes politeness, respect, and professionalism, while appreciating the contributions of all teachers and staff. Recommendations: (1) For school principals: These values provide a leadership foundation for building a positive and inclusive school culture. (2) For teachers: To align with the principal's leadership based on local values. (3) For the government: To evaluate principals using criteria grounded in local noble values. (4) For future researchers: As a reference for exploring local values in school leadership, particularly in Central Kalimantan.